Wrinkle Improvement in HanDam (Twist) on Ultraviolet B Irradiation-Induced Skin Photoaging in Hairless Mice - Inbong Song; Judong Song; Ilseok Jang; Dayoung Noh; Chaemyeong Lee; Jungkee Kwon (Applied Sciences)
Background: Skin photoaging caused by ultraviolet B (UV-B) irradiation leads to the formation of wrinkles. A method to lessen wrinkles is the application of Polydioxanone (PDO) lifting threads. HanDam (Twist) is a PDO lifting thread with a unique morphological twisted shape. Objective: The aim of this study was to evaluate the wrinkle improvement ability of HanDam (Twist) on UV-B irradiation-induced skin photoaging in a hairless mouse model. Methods: Wrinkles were induced by UV-B irradiation to the backs of female hairless mice for six weeks. After induction, the wrinkles were treated with threads, and the mice were monitored for six weeks post-treatment. Results: Our results showed that treatment with HanDam (Twist) effectively ameliorated UV-B irradiation-induced wrinkle depth and significantly increased collagen density by 13% compared to HanDam (non-Twist) in the histological analysis. In measuring protein expression related to collagen production, HanDam (Twist) significantly increased transforming growth factor beta (TGF-β) and collagen type 1 (COL1) by 46% and 67% compared to HanDam (non-Twist). Matrix metalloproteinase-1 (MMP-1) protein expression showed similar density and no significance compared to HanDam (non-Twist). Conclusions: These findings suggest that HanDam (Twist) improves the effectiveness of lifting threads for skin care compared to that of existing products.